LDPC code design for quadrature-quadrature phase shift keying - Wang, F.; Liu, Jian; Wang, S. (2017)
© 2017 IEEE. We introduce a model of a combination of particular low density parity check (LDPC) code and quadrature-quadrature phase shift keying (Q2PSK) constellation for the application of the downlink of the unmanned aerial vehicle (UAV) data chain. This model is a modification of the combination of LDPC code and constant envelope Q2PSK (CEQ2PSK) constellation. It achieves higher bandwidth efficiency of 4/3 times while ensures high power utilization and not increases the complexity of the algorithm implementation. The encoding algorithm of the particular LDPC code which can make the envelope of the output signal of Q2PSK to be a constant is the focal point of this paper. However, the model we proposed suffers from a loss of about 0.82dB compared with the unmodified model at bit error rate (BER) of 10-6. Considering the downlink is mainly used to transmit telemetry image data, and the impact of 0.82dB on such data is reflected by the fact that the images restored at the receiving end are slightly blurred, so we believe that it is acceptable to use the sacrifice of 0.82dB reliability for higher bandwidth efficiency.